RESIDENTIAL COMPLEXES BUILT BEHIND THE STATE INDUSTRY BUILDING IN THE STRUCTURE OF THE CAPITAL’S ADMINISTRATIVE CENTRE OF KHARKIV IN THE 1920S AND 1930S - Didenko, K.; Gella О. (Municipal economy of cities. Series: «Economy science», 2023)
The article is devoted to the history of the formation and features of three residential complexes: Chervonyi Promyslovets (1929–1931, architect S. Kravets), Budynok Spetsialistiv (1934–1936, architect L. Lemish), Novyi Pobut (1930–1932, architect M. Pokornyi), located near the new administrative centre of then the capital of Soviet Ukraine—Kharkiv. These complexes were created in the late 1920s and early 1930s and reflected the architectural and urban planning ideas, explorations, and concepts relevant in the early twentieth century. These include the idea of the garden city and the concepts of the commune house and the housing factory. The residential complexes Chervonyi Promyslovets and Budynok Spetsialistiv are a direct embodiment of the concept of a housing estate, and Novyi Pobut is a partial embodiment of the concept of socialisation of everyday life through the elements of a communal house. Looking at the overall structure of the complex of the capital’s administrative centre of Kharkiv, with its residential quarters separated from the administration and business centre by a broad green boulevard, we can note that this urban structure embodies the idea of a garden city. The article contains a compositional characterisation of all three complexes and describes their functional content and transformations through time. The article documents significant changes in the spatial planning schemes and approaches to the design of urban living environments, from perimeter development to free planning of neighbourhoods. The description focuses on documenting the monuments of modernist architecture in the capital city of Kharkiv, which is extremely important for consolidating its pivotal role in the world history of the Modern Movement. Since the preservation of architectural heritage is an integral part of the strategy of the modern European state and a prerequisite for understanding the value of the historic urban landscape and individual architectural objects, it is of utmost necessity and importance to document the architectural and urban heritage of metropolitan Kharkiv. The collected and structured material on the history of the construction and formation of residential complexes belonging to the administrative centre of the metropolitan Kharkiv, their spatial, compositional, and functional features will become the basis for preserving the historical character of the buildings and further development of the district.